Pengaruh Tiktok Affiliate Marketing Dan Kemudahan Akses Aplikasi Terhadap Impulse Buying Konsumen (Study Kasus Pada Anak Muda Di Kabupaten Ponorogo) - Dian Fateekha lireeh; Moh. Faizin (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Marketing that is popular today is digital-based. Affiliate Marketing is a business system by marketing other people's products and services using the internet and an affiliate will get a commission when successfully selling the product. This ease of finding information triggers the occurrence of Impulse Buying behavior. This study aims to determine the influence of Tiktok Affiliate Marketing on consumer Impulse Buying, to determine the effect of easy application access on consumer Impulse Buying. The method in this study is a quantitative approach, a non-probability sampling technique totaling 96 respondents and using the purposive sampling method. The data analysis method uses classical assumption tests, namely validity tests and reliability tests, multiple linear regression tests with t tests and f tests, and determination coefficient tests. The method in this study is a quantitative approach, a non-probability sampling technique totaling 96 respondents and using the purposive sampling method. The data analysis method uses classical assumption tests, namely validity tests and reliability tests, multiple linear regression tests with t tests and f tests, and determination coefficient tests.